2012
DOI: 10.1177/0309133311434244
|View full text |Cite
|
Sign up to set email alerts
|

Control of atmospheric particles on diffuse radiation and terrestrial plant productivity

Abstract: Terrestrial plant productivity tends to increase under increasing but non-saturating photosynthetically active solar radiation when water, temperature and nutrients are not limiting. However, studies have shown that photosynthesis can also be higher under enhanced diffuse light despite a decrease in total irradiance. Clouds and atmospheric aerosols are two important variables that determine the total and proportion of diffuse light reaching the surface and thereby the rate of photosynthesis and carbon accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
202
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 220 publications
(233 citation statements)
references
References 116 publications
12
202
0
10
Order By: Relevance
“…9). These predictions align with previous observations of the diffuse light enhancement of primary productivity in agricultural and natural systems (Alton, 2008;Kanniah et al, 2012). However, it has been observed that, as LAI drops (e.g.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…9). These predictions align with previous observations of the diffuse light enhancement of primary productivity in agricultural and natural systems (Alton, 2008;Kanniah et al, 2012). However, it has been observed that, as LAI drops (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…However, it has been observed that, as LAI drops (e.g. in savannahs and peat lands), the positive effect of diffuse light on primary productivity often becomes nonsignificant (Kanniah et al, 2012(Kanniah et al, , 2013. Assuming that a drop in LAI tends to correlate with a lower canopy-level extinction coefficient, our model suggests that the photosynthetic benefit of direct light may become more pronounced in low-LAI systems.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations